Multicentre clinical evaluation of the safety and performance of a simple transperineal access system for prostate biopsies for suspected prostate cancer: The CAMbridge PROstate Biopsy DevicE (CamPROBE) study. (September 2020) - Gnanapragasam, Vincent J; Leonard, Kelly; Sut, Michal; Ilie, Cristian; Ord, Jonathan; Roux, Jacques; Prieto, Maria Consuelo Hart; Warren, Anne; Tamer, Priya
Objectives: To report the prospective multicentre clinical evaluation of a first-in-man disposable device, Cambridge Prostate Biopsy Device, to undertake local anaesthetic outpatient transperineal prostate biopsies. Material and methods: Disposable single-use Cambridge Prostate Biopsy devices were manufactured based on a previous prototype. The lead site developed a user training course and disseminated the method to other sites. The Cambridge Prostate Biopsy Device (CamPROBE) was offered as an alternative to transrectal ultrasound guided biopsy to men due for a biopsy as part of their clinical management. Data on safety (infections and device performance), clinical utility, patient reported experience, biopsy quality and cancer detection were collected. Procedure time and local anaesthetic use was recorded in the lead site. The study was funded by a United Kingdom National Institute for Health Research (NIHR) i4i product development award. Results: A total of 40 patients were recruited (median age 69 y) across six sites; five sites were new to the procedure. Overall, 19/40 were first prostate biopsies and 21/40 repeat procedures. Both image-targeted and systematic biopsy cores taken. There were no infections, device deficiencies or safety issues reported. The procedure was well tolerated with excellent patient-reported perception and low pain scores (median of 3, scale 0–10). Histopathology quality was good and the overall cancer diagnosis rate (first diagnostic procedures) was 68% (13/19) and for significant cancers (⩾ histological Grade Group 2), 47% (9/19). In the lead centre (most experienced), median procedure time was 25 minutes, and median local anaesthetic use 11 ml ( n =17). Conclusions: Data from this device evaluation study demonstrate that the United Kingdom-developed Cambridge Prostate Biopsy Device/method for transperineal biopsies is safe, transferable and maintains high diagnostic yields. The procedure is well tolerated by patients, suited to the local anaesthetic outpatient setting and could directly replace transrectal ultrasound guided biopsy. Level of evidence: Level III